Surah An-Nahl 126 dalam Perspektif Pendidikan Islam - Intan Fazira; Khairunissa Khairunissa; Sinar Hafif Yulistia; M. Luthfi Khoiri (Jurnal Ilmiah Profesi Pendidikan, 2023)
Education is a very crucial issue. Education is presented as nothing but a process to optimize human potential, because the human soul is always dynamic, in process, never frozen, and always moves actively to achieve balance within a certain span of time. Islamic education has an educational concept known by several terms, "at-tarbiyah, at-ta'lim, and at-ta'dib". After all, the term has its own meaning that is different from one another. In order to understand the Qur'an, many Muslims have focused their knowledge on interpreting the Qur'an so that mufassir was born with various works discussing the holy book of the Qur'an. Al-Qur'an is a source of knowledge, in it teaches various aspects of life including education. Every verse mentioned in the Qur'an has significant meanings and values, and the values contained are as educational and life lessons for human life. There are also several verses of the Al-Quran which explain the values of education, both in the form of the object, the purpose, as well as the method. In this paper the author intends to discuss Islamic educational methods in the Qur'an. Education is an effort made by a person (educator) to his target (students) to realize a change in the target's behavior from not knowing to knowing, wrong to right and bad to good. Not far from Islamic education, "Islamic education as a process of developing the potential of students, aims to realize human beings who believe and fear Allah, are intelligent, skilled, have a high work ethic, are virtuous and are responsible for themselves, the nation and the nation. as well as religion. Surah an-Nahl consists of 128 verses.